Controlling the density of storable charge of surface faradaic layers on Fe2O3 photoanodes for solar rechargeable devices. Issue 8 (2nd February 2023) - Jiang, Dongjian; Sun, Xiao; Xue, Mengfan; Wang, Pin; Yao, Yingfang; Luo, Wenjun; Zou, Zhigang
Abstract : The density of storable charge (DOSC) is introduced as the number of charges stored in a surface faradaic layer of a semiconductor, and it can be used to describe the charge transfer kinetic process in semiconductor/electrolyte interfaces. Abstract : Interface charge transfer plays a key role in a photoelectrochemical cell. Recently, a faradaic junction transfer model was proposed that describes the interface charge transfer process. Electrochemical potential is introduced as a thermodynamic descriptor for the structure and composition of the surface faradaic layer of a semiconductor. However, the kinetic process in the faradaic junction model remains unclear. Herein, we introduce a descriptor, the density of storable charge (DOSC), to describe the number of charges that can be stored in a surface faradaic layer at different applied potentials. Moreover, the DOSC of the faradaic layer on the surface of Fe2 O3 was modified by Ti doping, and the results suggest that a larger DOSC leads to higher transient photocurrent in a solar rechargeable device, which is helpful for designing other high-performance devices for solar conversion and storage.